2017
DOI: 10.3390/ijms18071416
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Binding Site Stimulants of NMDA Receptors Alleviate Extrapyramidal Motor Disorders by Activating the Nigrostriatal Dopaminergic Pathway

Abstract: Dysfunction of the N-methyl-d-aspartate (NMDA) receptor has been implicated in the pathogenesis of schizophrenia. Although agonists for the glycine-binding sites of NMDA receptors have potential as new medication for schizophrenia, their modulation of antipsychotic-induced extrapyramidal side effects (EPS) has not yet been clarified. We herein evaluated the effects of glycine-binding site stimulants of NMDA receptors on antipsychotic-induced EPS in mice and rats. d-cycloserine (DCS) and d-serine significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The present observations provide a framework to examine other agents, including novel glycine site agonists, like Rapastinel [93] and NSX-2925 [14], the uptake inhibitors TASP0315003 [88] and bitopertin [35,36], D-amino acid oxidases inhibitors like sodium benzoate [22,106], and inhibitors of kynurenine aminotransferase II all of which modify PFC glutamatergic signalling [107,108]. Furthermore, it would be interesting to study agents acting at the neuronal alanine-serinecysteine-1 transporter which is implicated in the control of extracellular D-serine and glycine [8,109].…”
Section: General Discussion and Broader-clinical Relevance Of The Prementioning
confidence: 97%
“…The present observations provide a framework to examine other agents, including novel glycine site agonists, like Rapastinel [93] and NSX-2925 [14], the uptake inhibitors TASP0315003 [88] and bitopertin [35,36], D-amino acid oxidases inhibitors like sodium benzoate [22,106], and inhibitors of kynurenine aminotransferase II all of which modify PFC glutamatergic signalling [107,108]. Furthermore, it would be interesting to study agents acting at the neuronal alanine-serinecysteine-1 transporter which is implicated in the control of extracellular D-serine and glycine [8,109].…”
Section: General Discussion and Broader-clinical Relevance Of The Prementioning
confidence: 97%
“…Antipsychotics likely cause EPS via dopamine type 2 receptor blockade in the striatum. In a pre-clinical mouse study (129), both D-serine (300 mg/kg) and sodium benzoate (600 mg/kg) administered intraperitoneally attenuated haloperidol induced bradykinesia. D-serine showed a U-shaped curve for attenuation, as no effects were seen for 100 or 1,000 mg/kg doses.…”
Section: D-serine and Extrapyramidal Effectsmentioning
confidence: 99%
“…Consistent with this notion, brain ageing is associated with the reduced NMDA receptor function, in turn leading to declined memory and learning performance [78]. Stimulation of glycine binding to NMDA receptors have been shown to ameliorate extrapyramidal symptoms of neuromuscular function [79] and a study has shown that glycine administration could improve extrapyramidal and cognitive symptoms in Schizophrenic patients [54]. NMDA receptors have also been implicated in other age-related diseases such as diabetes [80] and hypertension [81].…”
Section: Discussionmentioning
confidence: 98%